2013
DOI: 10.1038/ncomms3092
|View full text |Cite
|
Sign up to set email alerts
|

Caesium accumulation in yeast and plants is selectively repressed by loss of the SNARE Sec22p/SEC22

Abstract: The non-essential cation caesium (Cs þ ) is assimilated by all organisms. Thus, anthropogenically released radiocaesium is of concern to agriculture. Cs þ accumulates owing to its chemical similarity to the potassium ion (K þ ). The apparent lack of a Cs þ -specific uptake mechanism has obstructed attempts to manipulate Cs þ accumulation without causing pleiotropic effects. Here we show that the SNARE protein Sec22p/SEC22 specifically impacts Cs þ accumulation in yeast and in plants. Loss of Saccharomyces cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…This effect was linked to a compromised vacuolar deposition. A similar effect was observed in a loss-of-function mutant of A. thaliana orthologue SEC22 (Draxl et al 2013).…”
Section: Involvement Of Vesicle Trafficking In Hm Transportsupporting
confidence: 68%
“…This effect was linked to a compromised vacuolar deposition. A similar effect was observed in a loss-of-function mutant of A. thaliana orthologue SEC22 (Draxl et al 2013).…”
Section: Involvement Of Vesicle Trafficking In Hm Transportsupporting
confidence: 68%
“…Furthermore, Adams et al (2013) reported that cesium inhibits the growth of plants via the jasmonate (JA; a lipid-based hormone) signal pathway, which regulates a wide range of processes in plants [ 12 ]. Dräxl et al (2013) showed how internal accumulation of cesium can be suppressed in plants via a mutation in a type of SNARE (Sec22p/SEC22) protein that plays a primary role in vesicle fusion [ 13 ]. By applying suppression-subtractive hybridization (SSH) and RT—PCR methods, some Cs-stress responsive genes were identified and analyzed [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Growth retardation caused by high concentrations of Cs + has been shown to be, at least partly, mediated through the jasmonate pathway, a phytohormone pathway which is mainly involved in biotic and abiotic stress responses9. Recent studies have also suggested that Cs + is sequestrated in vacuoles and a SNARE protein SEC22 may be responsible for Cs + deposition in vacuoles1011.…”
mentioning
confidence: 99%